Structural and Morphological Properties of as-Deposited and Heat -Treated Composite (CuPc/Alq3) Thin Films - Hassan, Zahraa Majed; Abdulameer, Ameer F. (Iraqi Journal of Science, 2023)
In this work, an organic semiconductor of copper (II) phthalocyanine (CuPc) and Tris(8-hydroxyquinoline) aluminum (III) (Alq3) were entirely dissolved in chloroform with various mixing ratios (1:0,0.75:0.25,0.5:0.5,0.25:0.75,0:1) (w/w) to make thin films. They were deposited on a pre-cleaned glass using a spin-coating process and heat-treated at 473 K in vacuum. X-ray diffraction and a scanning electron microscope were used to investigate the films. XRD analysis reveals that CuPc/Alq3 composites have a polymorphic structure, with the exception of Alq3’s amorphous structure, the crystallinity increases after annealing, but decreases when the concentration of Alq3 is increased. The quantity of (CuPc) rod-like structure and (Alq3) grain-like islands structure depends on the percentage of the combination. The compositional parameters of as-deposited and annealed thin films were explained using EDX data, which revealed that the sample was close to the nominal composition.